2017
DOI: 10.1186/s12943-017-0610-2
|View full text |Cite
|
Sign up to set email alerts
|

ITIH5 mediates epigenetic reprogramming of breast cancer cells

Abstract: BackgroundExtracellular matrix (ECM) is known to maintain epithelial integrity. In carcinogenesis ECM degradation triggers metastasis by controlling migration and differentiation including cancer stem cell (CSC) characteristics. The ECM-modulator inter- α-trypsin inhibitor heavy chain family member five (ITIH5) was recently identified as tumor suppressor potentially involved in impairing breast cancer progression but molecular mechanisms underlying its function are still elusive.Methods ITIH5 expression was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(77 citation statements)
references
References 94 publications
14
62
1
Order By: Relevance
“…(A) Heatmap illustrates an ITIH5‐associated signature of genes known being associated with metastasis ( P < 0.001). Comparison of gene expression profiles was performed using whole genome expression data of independent ITIH5‐expressing (ΔpBK‐ITIH5 clones) and ITIH5‐deficient MDA‐MB‐231 ΔpBK‐mock single‐cell clones including the MDA‐MB‐231 WT. The heatmap of significantly ( P ≤ 0.05) differential expressed (red: overexpressed; blue: suppressed) genes is shown.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(A) Heatmap illustrates an ITIH5‐associated signature of genes known being associated with metastasis ( P < 0.001). Comparison of gene expression profiles was performed using whole genome expression data of independent ITIH5‐expressing (ΔpBK‐ITIH5 clones) and ITIH5‐deficient MDA‐MB‐231 ΔpBK‐mock single‐cell clones including the MDA‐MB‐231 WT. The heatmap of significantly ( P ≤ 0.05) differential expressed (red: overexpressed; blue: suppressed) genes is shown.…”
Section: Resultsmentioning
confidence: 99%
“…As we recently demonstrated that ITIH5 mediates an epigenetic shift in breast cancer cells, we analyzed ENG promoter methylation in different MDA‐MB‐231 single cell clones by performing MSP (Supplementary Figure S2A). MDA‐MB‐231 WT and mock clones were found being completely methylated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations